2006
DOI: 10.1063/1.2182020
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of two-pole X-band HgBa2CaCu2O6+δ microstrip filters

Abstract: Articles you may be interested inTriple-band high-temperature superconducting microstrip filter based on multimode split ring resonator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Sample degradation due to the photolithographic process can therefore be minimized. Recently, we have fabricated Hg-1212 two-pole X-band microstrip filters and showed lower insertion loss of 0.70 0.04 dB at 110 K than that of YBCO and Cu at 77 K [12]. These results have shown that Hg-1212 may present a promising alternative material for passive microwave applications at high operation temperatures above 77 K.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Sample degradation due to the photolithographic process can therefore be minimized. Recently, we have fabricated Hg-1212 two-pole X-band microstrip filters and showed lower insertion loss of 0.70 0.04 dB at 110 K than that of YBCO and Cu at 77 K [12]. These results have shown that Hg-1212 may present a promising alternative material for passive microwave applications at high operation temperatures above 77 K.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the sensitivity of the Hg-1212, when containing certain amount of impurity phases, to water or water-based chemicals used in the standard photolithography process makes processing of Hg-1212 devices challenging. With the development of a cation exchange process [14], [15], the fabrication and processing difficulties have been greatly eased and some interesting microwave properties have been demonstrated in Hg-1212 films and devices [3], [12], [13]. For example, it has been shown that Hg-1212 has a comparable microwave surface resistance and power handling capability at 110 K to that of YBCO and Tl-2212 at 77 K [3], [13].…”
Section: Introductionmentioning
confidence: 95%
“…By translating the precursor's crystalline lattice to the Hg-HTS film, the major difficulties in epitaxy of Hg-HTS films, which is caused by the severe reaction of Hg vapour with substrates and the volatility of Hgrelated compounds, have been circumvented. Epitaxial Hg-1212 films on both oxide and metal substrates have been obtained with superior physical properties demonstrated for dc and rf applications [11][12][13][14]. Nevertheless, the microscopic mechanism of the cation exchange has been under debate and understanding this mechanism is of great importance to application of the cation-exchange method to other volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, two-pole X-band microstrip filter on a singlesided HgBa 2 CaCu 2 O 6þd (Hg-1212) film of 5 mm  10 mm could work at 110 K. 6 However, the growth of large-area epitaxial Hg-based HTS thin films with uniformity is difficult. Compared to the Hg-based HTS thin films, large-area doublesided Tl-based HTS thin films (Tl-2212) have been prepared successfully on different substrates.…”
mentioning
confidence: 99%